Ge-doped Li4Ti5-xGexO12 (x = 0.05) as a fast-charging, long-life bi-functional anode material for lithium- and sodium-ion batteries. Issue 10 (July 2020) - Ali, Basit; Muhammad, Raz; Anang, Daniel Adjah; Cho, Min-kyung; Kim, Ji-Young; Nam, Kyung-Wan
Abstract: We explored the doping effect of Ge 4+ on the Li4 Ti5- x Ge x O12 ( x = 0.0 and 0.05) anode material by looking at its electrochemical performance in both Li- and Na-ion batteries. Combined analysis using Rietveld refinement of high-resolution powder diffraction (HRPD) and transmission electron microscopy (TEM) unambiguously identified homogeneous Ge doping into the 16 c octahedral Ti site of the Li4 Ti5 O12 (LTO) cubic spinel structure. This Ge doping leads to a much-reduced particle size, slightly expanded lattice and increased electrical conductivity due to the increased Ti 3+ to Ti 4+ ratio, these results were verified by HRPD, scanning electron microscopy (SEM), 4-point probe and x-ray photoelectron spectroscopy (XPS) analysis. The Li4 Ti4.95 Ge0.05 O12 (Ge0.05-LTO) electrode shows much-improved capacity, high-rate capability and excellent cycling stability in a Li-half cell compared with an un-doped LTO electrode. This performance improvement is due to the reduced Li + diffusion path and faster Li + insertion/extraction kinetics that originate from Ge doping. In addition to these results, when tested as an anode for SIBs, the Ge0.05-LTO electrode exhibits enhanced capacity and cycling stability compared to un-doped LTO electrode, demonstrating its bi-functional, advantageous features in both LIB and SIB systems.